Survey, identification, and pathogenicity of Ceratocystis fimbriata complex associated with wilt disease on Acacia mangium in Malaysia - Syazwan, Samsuddin Ahmad; Mohd Farid, Ahmad; Wan Muhd Azrul, Wan Azhar; Muhammad Syahmi, Hishamuddin; Mohd Zaki, Abdullah; Ong, Su Ping; Mohamed, Rozi (MDPI AG, 2021)
Ceratocystis wilt disease surveys were conducted in three selected Malaysian Acacia mangium plantations. These completed surveys revealed the occurrence of the wilt disease, with the incidence of infection ranging from 7.5% to 13.6%. Signs of wood-boring insects, bark peeling due to squirrel activity, and pruning wounds were often associated with this disease. The fungus most frequently isolated from the diseased trees was the Ceratocystis fungus. The analysis on the morphological characteristics has identified the fungus as Ceratocystis fimbriata complex. Phylogenetic analysis based on the sequences of the ITS, and concatenated sequences of EF1α-βT regions grouped the isolates within the C. fimbriata sensu stricto, in comparison to other C. fimbriata isolates. Pathogenicity tests were conducted on six to nine-month-old healthy A. mangium seedlings by inoculating these seedlings with eight out of the 16 isolates. The results demonstrated that all the isolates were pathogenic, with mortality beginning as early as two weeks after inoculation. However, an ANOVA test indicated a significant difference between the pathogenicity levels among the fungal isolates. The results also showed that pathogen aggressiveness was not correlated with geographical origin. A host range test was also conducted by using C. fimbriata SSB3 and FRIM1162 isolates against several forest plantation species. The findings suggested that only A. mangium was susceptible to C. fimbriata. The other species remained healthy with no symptoms of infection even after seven weeks of treatment, as compared to the A. mangium species, where between 38 to 60% of the inoculated plants had died. This study provides new information on the status of Ceratocystis wilt disease, especially on the occurrence and effects on A. mangium plantation, by giving insights on how to control and manage this ferocious plant pathogen in the future.